2012
DOI: 10.5194/we-12-33-2012
|View full text |Cite
|
Sign up to set email alerts
|

Invasive acacias experience higher ant seed removal rates at the invasion edges

Abstract: Abstract. Seed dispersal is a key process for the invasion of new areas by exotic species. Introduced plants often take advantage of native generalist dispersers. Australian acacias are primarily dispersed by ants in their native range and produce seeds bearing a protein and lipid rich reward for ant mutualists (elaiosome). Nevertheless, the role of myrmecochory in the expansion of Australian acacias in European invaded areas is still not clear. We selected one European population of Acacia dealbata and anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
0
16
2
Order By: Relevance
“…and Pinus pinaster . In Tocha, the mean annual precipitation is 948 mm and the mean annual temperature is 16.2 °C (Montesinos, Castro & Rodríguez‐Echeverría, ).…”
Section: Methodsmentioning
confidence: 99%
“…and Pinus pinaster . In Tocha, the mean annual precipitation is 948 mm and the mean annual temperature is 16.2 °C (Montesinos, Castro & Rodríguez‐Echeverría, ).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, massive seed production and accumulation is highly variable within acacias . Once released, seeds can be dispersed by water or wind, but also through myrmecochory (seeds with elaiosomes) or ornithochory (seeds with arils) (French and Major 2001;Richardson and Kluge 2008;Marchante et al 2010;Montesinos et al 2012), remaining viable for up to 150-200 years (Daws et al 2007;Leino and Edqvist 2010).…”
Section: Reproductive Featuresmentioning
confidence: 99%
“…In addition to changes in mutualistic interactions, invasive species frequently develop locally adapted traits as a response to the different environmental conditions found in their nonnative ranges (Hierro et al 2005). Plant traits can differ among different areas within a single non-native region, showing, in some cases, differences between the expanding invasion edges and mature invaded areas (Phillips et al 2006(Phillips et al , 2007Lankau et al 2009;Montesinos et al 2012). Recent studies showed that acacias from non-native populations were investing more resources into seed mass than acacias from native populations, but proportionally less resources in elaiosomes than their conspecifics in the native range (Correia et al 2016).…”
Section: Introductionmentioning
confidence: 99%